Home treatment of fragile patients with acute pulmonary embolism: a subgroup analysis of the multinational home treatment of pulmonary embolism (HoT-PE) trial. (25th November 2020) - Hobohm, L; Anusic, T; Konstantinides, S.V; Barco, S
Abstract: Background and aims: Subgroup analyses of randomized trials and cohort studies on direct oral anticoagulants (DOACs) suggested that single direct drug treatment may be effective and safe in elderly and "fragile" patients with acute pulmonary embolism (PE). In a post-hoc analysis of HoT-PE, a prospective multicenter management trial, we studied whether early discharge and home treatment of acute PE is effective and safe in these patients. Methods: HoT-PE enrolled patients with acute PE classified as being at low risk based on the modified Hestia criteria and the absence of right ventricular dysfunction. The primary efficacy outcome was symptomatic recurrent VTE, or PE-related death within 3 months of enrolment. The safety outcome included major bleeding. Fragility was defined as age >75 years, a creatinine clearance level <50 ml/min, or a body mass index <18.5 kg/cm 2 . Results: A total of 524 patients were included; of these, 112 (21.4%) were fragile. Mean age was 77 (range 74–80) years. A total of 104 (92.9%) fragile and 372 (90.3%) non-fragile patients spent two nights or less in hospital corresponding to a median hospital stay of 42 (Q1-Q3: 25–47) and 32 (Q1-Q3: 23–46) hours, respectively. The primary efficacy outcome occurred in one (0.9%) fragile and one (0.5%) non-fragile patient (absolute risk difference [ARD] +0.4%; 95% CI: −1.1%; +4.4%). Major bleeding occurred in three (2.7%) fragile and three (0.7%) non-fragile patients; ARD +2.0% (+0.3%; +6.9%). All-cause 3-month mortality was low in both groups (0.9% vs. 0.2%; ARD +0.7%, −0.7%; +4.7%). Conclusion: Early discharge and home treatment of fragile patients with acute PE appears to be feasible and acceptably safe. The HoT-PE trial supports the notion that these patients should not be a priori excluded from early discharge, but caution is warranted due to a possibly higher risk of major bleeding on DOAC treatment. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This study was supported by the German Federal Ministry of Education and Research (BMBF 01EO1503).